2021
DOI: 10.47440/jafe.2021.2409
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of digested rotten potato (Solanumtuberosum) used as a production medium of spirulina (Spirulinaplatensis)

Abstract: The study was conducted to evaluate physico-chemical properties of digested rotten potato (Solanum tuberosum) used as a production medium of spirulina in sixteen days after twenty six days digestion. Three exclusive concentrations such as 20%, 40% and 60% of DRP (digested rotten potato) were used. Spirulina changed into inoculated in supernatant DRP for a period of 14 days. Light intensity (lux/m 2 /s) was varied from 2725 ± 30, 2720 ± 32 and 2730 ± 34, respectively on first day to 2740 ± 30, 2780 ± 27 and 269… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…have not yet been studied elsewhere. Some previous studies demonstrated that DRPS had promising effects for enhancing the growth and biochemical composition of Spirulina platensis [22,33]. In the present study, DRPS showed superior biomass production of M. littorale, which is far higher than other agricultural wastes including rotten tomatoes for S. platensis [34] and aquaculture waste for Chlorella vulgaris [35].…”
Section: Introductionsupporting
confidence: 46%
“…have not yet been studied elsewhere. Some previous studies demonstrated that DRPS had promising effects for enhancing the growth and biochemical composition of Spirulina platensis [22,33]. In the present study, DRPS showed superior biomass production of M. littorale, which is far higher than other agricultural wastes including rotten tomatoes for S. platensis [34] and aquaculture waste for Chlorella vulgaris [35].…”
Section: Introductionsupporting
confidence: 46%